Gynecological pre participation examination–a new proposal for female athletes care. Issue 4 (27th March 2011) - Parmigiano, T; Zucchi, E; Araujo, M; Negra, L; Guindalini, C; Castro, R; Moreno, C; Girão, M; Cohen, M; Sartori, M
Abstract : Background: Female athletes are unaware of the influence of sports practice on health and usually do not report sexual or gynecological complaints during a regular Pre Participation Examination (PPE). Objective: To propose a gynecological PPE for female athletes, assessing questions regarding unsupervised sports practice, sexual transmitted diseases, as well as consciousness of the coaches regarding their gynecological health. Design: Observational cross-sectional study. Settings/Patients: A total of 148 athletes participating in regular and competitive sports at the 'Olympic Center of Training and Research for youth athletes' in São Paulo – Brazil, during the first semester of 2010. Parents/guardians signed the informed consent form. Intervention: The athletes participated in an informative lecture about relevant gynecological questions related to their health and sports practice. Subsequently, the subjects responded to a questionnaire evaluating gynecological features, together with the Incontinence Questionnaire-Short Form (ICIQ-SF) and Eating Attitudes Test (EAT-26). Results: The study assessed 148 athletes, mean age of 15.4 ± 2.0 years, reporting 10.9 ± 4.0 h of practice/week. 50% of the participants described irregular menstrual interval, 23.0% ignored the meaning of sexual transmitted diseases and 72.4% had never been to a gynecological appointment. A total of 23.1% of the athletes complained of urine loss and 14.5% should be evaluated by a nutritionist regarding alimentary disturbance or use of diuretics or laxative for weight loss. Moreover, 89.0% ignored the occurrence of urinary incontinence in athletes and the definition of female athlete triad, and 81.9% affirmed that would not mention these questions to their coaches even if this would improve their health or performance. Conclusion: The gynecological issues are usually underestimated in the follow up of female athletes. The PPE could be an excellent opportunity to provide a special care to young competitors, improving their knowledge about their body and health and most likely, their goals.